Infant Language Acquisition (A Case Study on Bilingualism) - Fajrinur Fajrinur (English LAnguage Study and TEaching, 2021)
The purpose of this study is to describe a language development at a very young age. The method of the study was descriptive method. The data was collected from NR who was 1.2 years old girl. In collecting the data, the researcher observed her interaction at home and interviewed NR and her mother. Every word the researchers understand from her was written down, described, and classified. From the data, the researcher concluded that NR understood and spoke both languages equally. She used the same amount of words from both Bahasa Indonesia and Acehnese.She also showed the ability to differentiate between the two languages when she talked. She can easily switch from one language to another depend on who she was taking to. This shows an early sign of bilingualism.